أثر العرف في أحكام الزواج وانحلاله في الفقه الإسلامي والتشريع الجزائري: دراسة تحليلية مقارنة - منصور محمد (Universty Of El-oued جامعة الوادي, 2024)
تناولت هذه الأطروحة موضوعًا هامًّا تعلَّق بـــ: أَثَرِ الْعُرْفِ فِي أحكام الزَّواج وانحلاله في الفقه الإسلاميِّ والتَّشريع الجزائريِّ-دراسة تحليلية مقارنة-، وعن إشكاليتها الرئيسة تمثلت في: كيف أثَّر العرف على تسطير الأحكام المتعلِّقة بالزَّواج وانحلاله في الفقه الإسلاميِّ والتَّشريع الجزائريِّ؟ وقد أجابت الدِّراسة عن ذلك من خلال فصل تمهيدي، وبابين في كلٍّ منهما فصلان، فالفصل التَّمهيدي تناولت فيه مفهوم العرف وحُجِّيته وأدواره، والباب الأوَّل قسَّمته لفصلين؛ فخصَّصت الأوَّل منهما لأثر العرف في أحكام مقدِّمات الزَّواج (الخِطبة)، والثَّاني تحدَّثت فيه عن أثر العرف في أحكام الزَّواج. أمَّا الباب الثَّاني فقد جعلته أيضًا في فصلين؛ فتكلَّمت في الأوَّل منهما عن أثر العرف في طرق انحلال الزَّواج، وفي الثَّاني عن أثر العرف في آثار انحلال الزَّواج، وكلُّ ذلك بين الفقه الإسلاميِّ والتشريع الجزائريِّ. وتوصلت الدَّراسة لجملة من النتائج لعلَّ من أهمِّها: أنَّ العرف حُجَّة ويعتبر أصلًا ينبني عليه شطر عظيم من أحكام الفقه الإسلاميِّ، وأنَّه دليل يمكن للمشرِّع الجزائريِّ أن يستأنس به لإيجاد حلٍّ للمسائل المسكوت عنها في قانونه للأسرة. أنَّ فقهاء الشَّريعة الإسلاميِّة قد أخذوا بالعرف في كثير من مسائل الزَّواج وانحلاله على عكس المشرِّع الجزائري الذي أخذ به في بعض نصوصه وفي القليل من اجتهاداته القضائية سواء كان ذلك بشكل صريح أو ضمني. وممَّا نوصي به هو مراجعة الأحكام الشَّرعيَّة المتغيرة والنصوص القانونية والاجتهادات القضائية التي مرجعها العرف، والنَّظر فيها حتى تواكب المستجدات. كما ندعو الجهات التَّشريعية والقضائيَّة وشؤون الفتوى أن تدون الأعراف الجارية المعتبرة للحاجة إليها في الحكم، ولتمكين الباحثين من الاطلاع عليها. This dissertation explores the crucial topic of marriage and its dissolution within the framework of Islamic jurisprudence and Algerian legislation, with a focus on the impact of custom. It presents an analytical comparative study, addressing key questions such as: How has custom influenced the formulation of provisions related to marriage and its dissolution in Islamic jurisprudence and Algerian legislation? The study is structured into a preliminary chapter and two main parts, each consisting of two chapters. The preliminary chapter examines the concept of custom, its authority, and its roles. Part One includes two chapters: the first chapter describes the influence of custom on engagement provisions, while the second discusses its impact on marriage provisions. Part Two also comprises two chapters: the first chapter addresses the effects of custom on the methods of dissolving a marriage, and the second examines the effects of marriage dissolution, comparing Islamic jurisprudence and Algerian legislation. Key conclusions of the study include: Custom is recognized as an authoritative source in Islamic jurisprudence and serves as a basis for many provisions, potentially offering solutions for Algerian legislators in areas where family law is not explicit. While Islamic jurists extensively incorporate custom in matters of marriage and its dissolution, Algerian legislators have only partially adopted these customs, whether explicitly or implicitly, in some texts and judicial interpretations. The study recommends reviewing Sharia provisions, legal texts, and judicial interpretations based on custom in light of modern developments. It also urges legislative, judicial, and fatwa authorities to document recognized customs, as they are essential for rulings and should be accessible to researchers.
أطروحة دكتوراه تخصص الشريعة و القانون في العلوم الإسلامية
Keywords: العرف - أحكام الأسرة – الطلاق – الشريعة الإسلامية – قانون الأسرة; Custom - Family Law - Divorce - Islamic Law - Family Law